Intervening to Enhance The Occupational Performance of Children With Obstetrical Brachial Plexus Palsy: A Randomized Controlled Trial - (:unkn) unknown (TURKEY ASSOC PHYSIOTHERAPISTS, 2021)
Purpose: To investigate the benefits of intervening to enhance the occupational performance of children with obstetrical brachial plexus palsy (OBPP). Methods: Twenty- nine children with OBPP, 4-7 years aged, participated in this study. Intervention group composed of six girls and 12 boys. They participated in 40 minutes to 36 sessions of intervention. Both intervention and control group children' occupational performance issues were determined by the COPM. The Pediatric Evaluation of Disability Inventory (PEDI) used for evaluating the function in children and level functional independence of a child in activities of daily living was evaluated with The Functional Independence Measure for Children (WeeFIM). Results: COPM, PEDI, WeeFIM scores demonstrated statistically significant improvement (p<0.01) in occupational performance in the intervention group. Significant correlations were found between COPM performance and PEDI (p<0.01) in change scores. Conclusions: The present study is the first study about occupational performance intervention with COPM application in the children with OBPP. The present study suggests intervening to enhance the occupational performance and COPM as useful for the children with OBPP.
Keywords: activities of daily living; brachial plexus neuropathies; randomized controlled trial; PEDIATRIC EVALUATION; TURKISH CHILDREN; VALIDITY; PARTICIPATION